PENGEMBANGAN KEBIJAKAN INTEGRASI SISTEM MANAJEMEN MUTU DAN LINGKUNGAN BERKELANJUTAN Studi Kasus Kawasan Industri Jababeka, Cikarang, Bekasi - Aris Dwi Cahyanto (President University, 2016)
The purpose of this research is to analyze an integrated policy development of quality and environment management system. To achieve the purpose, researcher use multi dimensional scaling (MDS) method. MDS can use to analize sustainability status and leverage factors of tenant service. Result of this research show that tenant service reviewed from ecological, sociable, technological, institutional dimensions has less-sustainable status. However, when seen from its economical dimension, this tenant service matter is quite sustainable. Result of MDS describe that there were twenty three attributes which become to be leverage factor. The integrated policy development of quality and environment management system become to sustainable, if the area management direct policy to focus on institusional, technological, ecological and social dimensions.